2016
DOI: 10.1108/nfs-05-2015-0059
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality and safety of traditional smoked spotted tilapia fish (Tilapia mariae) from Lagos State, Nigeria

Abstract: Purpose – This study aims to assess the quality and microbial safety of traditional smoked spotted tilapia fish from Lagos State and, by doing so, determine the quality and microbial safety level of traditional smoked spotted tilapia fish, their distribution, effects and possible public health implications of the quality/rancidity indices and microorganisms on the consumers. Design/methodology/approach – Fresh spotted tilapia fish (100 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…These showed that there was a significant influence of processing parameters on proximate compositions of the dehydrated catfish in the present study. This agreed with the reports of Adeyeye et al (2016b) in assessing the quality and safety of traditional smoked spotted tilapia fish ( Tilapia mariae ) from Lagos State, Nigeria, and Chukwu and Shaba (2009) studied the effects of drying methods (kiln smoking at 60-70°C and electric oven drying at 120°C) on proximate compositions of whole catfish ( Clarias gariepinus ) of about 278 g each. However, Treatment 5 that gave the lowest MC (7.43 per cent) in this study could enhance the maintenance of quality during storage and the first ranking in overall acceptability of the corresponding dehydrated catfish sample in the preliminary sensory evaluation result (Table I) suggested this combination of processing parameters (6 per cent brine, 90 min and 110°C) as the best conditions for the production of good quality dehydrated catfish.…”
Section: Quality Assessment Of the Dehydrated Catfishsupporting
confidence: 86%
“…These showed that there was a significant influence of processing parameters on proximate compositions of the dehydrated catfish in the present study. This agreed with the reports of Adeyeye et al (2016b) in assessing the quality and safety of traditional smoked spotted tilapia fish ( Tilapia mariae ) from Lagos State, Nigeria, and Chukwu and Shaba (2009) studied the effects of drying methods (kiln smoking at 60-70°C and electric oven drying at 120°C) on proximate compositions of whole catfish ( Clarias gariepinus ) of about 278 g each. However, Treatment 5 that gave the lowest MC (7.43 per cent) in this study could enhance the maintenance of quality during storage and the first ranking in overall acceptability of the corresponding dehydrated catfish sample in the preliminary sensory evaluation result (Table I) suggested this combination of processing parameters (6 per cent brine, 90 min and 110°C) as the best conditions for the production of good quality dehydrated catfish.…”
Section: Quality Assessment Of the Dehydrated Catfishsupporting
confidence: 86%
“…Higher results were recorded in cooked Anchovy cake (46.59±0.79) by Inanli et al (2011), ln fish paste (77.23±0.04) and fish burger (65.58±0.46) by Mahmoudzadeh et al (2010). Lower results were recorded in smoked spotted tilapia fish samples (Adeyeye et al, 2016). Moisture content of fish is necessary for a number of biochemical reactions and physiological changes that could affect the stability and quality of fish.…”
Section: Discussionmentioning
confidence: 88%
“…(Table I). Although several studies recorded approximate protein per cent in various fish products (Adeyeye et al, 2016;Naila et al, 2011); however, lower protein %t was observed in some fish pastes and fish burgers from Iran (Mahmoudzadeh et al, 2010). The low protein content could be attributed to the processing conditions and the time of fish harvest (Kristinsson and Rasco, 2000;Rezaei and Hedayatifard, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies recorded approximate protein percent in various fish products (Naila et al, 2011;Adeyeye et al, 2016). The low protein content of the fish products could be attributed to the processing conditions and the time of fish harvest (Kristinsson and Rasco, 2000;Rezaei and Hedayatifard, 2013).…”
Section: Crude Protein Contentmentioning
confidence: 99%